Capoeira for beginners: self-benefit for, and community action by, new Capoeiristas. Issue 7 (2nd September 2019) - Jordan, M.; Wright, E. J.; Purser, A.; Grundy, A.; Joyes, E.; Wright, N.; Crawford, P.; Manning, N.
ABSTRACT: Capoeira could be defined as a Brazilian martial art and game to be played. This research explored how capoeira play might be considered to facilitate connectedness amongst newly-recruited persons, plus any other ramifications of capoeira involvement. A beginners' course of capoeira was provided to participants, free of charge, in an English city in the West Midlands—new capoeiristas in a new venue for capoeira. Researchers attended classes to collect/construct overt non-participant observation data. In addition, semi-structured interviews were undertaken with the new capoeiristas post-course. This article explores researchers' observation fieldnotes and interviewees' narratives. These qualitative data-driven debates include the concepts: self, identity, escapism, multiparty endeavour, community, temporality, enjoyment, and transcending boundaries. Capoeira is theorised in a fresh manner that highlights social benefits of capoeira—for example as an enjoyable and supportive group endeavour which includes elements of social play and community-building—plus benefits for self that can transcend the boundaries of the class. Findings highlight how capoeira can be considered an inherently multiparty endeavour whereby social actors form, and experience, a community in order to embrace capoeira play. Data suggest capoeira can facilitate group playfulness, joviality, and laughter. Further, capoeiristas can enact and experience—some mode of—escapism via capoeira, whereby new place and pursuit can facilitate hedonistic diversion from the mundane. Capoeira appears to provide adventure and liberation into a relatively unburdened part of, or place in, social life. Corporeal and discursive boundary-empowerment can also be experienced by capoeiristas, fostering positive identity work in the wider world. Capoeira can be argued to facilitate mutuality (e.g. community experience and group work) and egoism (e.g. an individual's identity work) concurrently. This research suggests that modified capoeira for beginners can be beneficial for both the new capoeiristas themselves and for positive community action during and beyond class.